2007
DOI: 10.1080/00319100601089752
|View full text |Cite
|
Sign up to set email alerts
|

Removal of organic dye pollutants from wastewater by electrochemical oxidation

Abstract: The removal of chemical oxygen demand (COD) and color from simulated dye wastewater containing organic dyes, direct yellow 4, C 26 H 20 N 4 O 8 S 2 Na 2 and acid yellow 17, C 16 H 10 O 7 N 4 S 2 Cl 2 Na 2 experimentally investigated using an electrochemical undivided cell reactor with Pt as anode and steel as cathode. Particular attention was paid to probe the effect of supporting electrolyte (NH 4 Cl), cell voltage, pH, and treatment time on the electrochemical treatment efficiency. Experiments were also carr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2008
2008
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…The PPy-Chi-CaFe 2 O 4 composite layer was prepared in different thicknesses in the range of 2.8 nm to 59.5 nm using Figure 6: The FT-IR results related to PPy-Chi-CaFe 2 O 4 sensing layer after the interaction with (a) MB and (b) MO. 7 International Journal of Polymer Science the electrodeposition technique. The composite layer was characterized with analytical methods including the FT-IR, FE-SEM, and XRD techniques, and they confirmed the CaFe 2 O 4 was formed in the polypyrrole and chitosan composite.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The PPy-Chi-CaFe 2 O 4 composite layer was prepared in different thicknesses in the range of 2.8 nm to 59.5 nm using Figure 6: The FT-IR results related to PPy-Chi-CaFe 2 O 4 sensing layer after the interaction with (a) MB and (b) MO. 7 International Journal of Polymer Science the electrodeposition technique. The composite layer was characterized with analytical methods including the FT-IR, FE-SEM, and XRD techniques, and they confirmed the CaFe 2 O 4 was formed in the polypyrrole and chitosan composite.…”
Section: Resultsmentioning
confidence: 99%
“…Many methods that are based on biological [5], chemical, and physical properties of materials [6] have been used to degrade MO and MB. The conventional methods including electrooxidation [7], electro-Fenton [8], adsorption [9], ozone [10], photocatalytic [11], and reverse osmosis [12]. The electrooxidation method is an attractive technique used to treat textile effluents [13], while decontamination of the wastewater depends on the work electrodes in electrochemical reactors [14].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, in the study of Silva et al, which showed the first-order removal of TOC, EE/M exhibited far greater variations with time (31–37%) than EE/O (6–11%) . However, by high current operations for utilizing the oxidant generation reaction, pollutant removal generally follows first-order kinetics in most EOPs, where the use of EE/O is practically appropriate. More details about the dependences of EE/O and EE/M on the operating parameters (including initial organic load and j ) are provided in the subsequent sections.…”
Section: Performance Evaluation Of Eopsmentioning
confidence: 99%
“…Optimized conditions under specified cost driven constraints were obtained at 6.7 mA/cm 2 , 5.9 mA/cm 2 and 5.4 mA/cm 2 current density and 3.1 g/L, 2.5 g/L and 2.8 g/L NaCl concentration for Levafix Blue CA, Levafix Red CA and Levafix Yellow CA reactive textile dyes, respectively. Parsa and Shojaat (2007) (NH 4 Cl) and increasing cell voltage. Szpyrkowicz and Radaelli (2007) studied and proposed the electro-oxidation of a spent dyeing bath, mediated by the Cl -/Cl 2 redox couple, as a technology alternative to hypochlorite oxidation.…”
Section: Physico-chemical Processesmentioning
confidence: 99%